2022
DOI: 10.3389/fneur.2022.826739
|View full text |Cite
|
Sign up to set email alerts
|

Vestibulo-Ocular Reflex Is Modulated by Noisy Galvanic Vestibular Stimulation

Abstract: We investigated whether noisy galvanic vestibular stimulation (nGVS) modulates the vestibulo-ocular reflex (VOR) and whether this effect is correlated with the effect of nGVS on body sway. Thirty healthy young adults participated. The video head impulse test (vHIT) was used to estimate the ratio of eye motion velocity/head motion velocity to VOR-gain. The gain 60 ms after the start of head motion (VOR-gain-60 ms) and regression slope (RS) (i.e., gain in eye and head motion; VOR-gain-RS) were calculated. The to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 41 publications
(71 reference statements)
0
10
0
Order By: Relevance
“…In contrast Matsugi et al (2022) found that nGVS significantly reduced rather than increased the video head impulse test (vHIT) gain to horizontal head impulses, indicating suppression of the VOR with nGVS. The reasons for these contradictory results are not clear.…”
Section: Integrated Analysis and Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…In contrast Matsugi et al (2022) found that nGVS significantly reduced rather than increased the video head impulse test (vHIT) gain to horizontal head impulses, indicating suppression of the VOR with nGVS. The reasons for these contradictory results are not clear.…”
Section: Integrated Analysis and Discussionmentioning
confidence: 78%
“…The varying nature of study designs and the sensory conditions utilized during assessment make it difficult to draw credible conclusions between studies ( Matsugi et al, 2020 ; McLaren et al, 2022 ). Of the current amplitudes set at a group level, 200 μA demonstrated significantly reduced postural sway in two studies ( Inukai et al, 2020a ; Nooristani et al, 2021 ), and no change in a further study ( Matsugi et al, 2022 ); 400 μA provided noted improvements in balance in four studies ( Inukai et al, 2018a , b , 2020b , c ) with no effect in one study. At 1,000 and 1,200 μA, the results were variable; balance improved in one study ( Inukai et al, 2018b ), deteriorated in one study ( Matsugi et al, 2020 ) but had no effect ( Nooristani et al, 2019b ; Matsugi et al, 2022 ), or had limited effect ( Nooristani et al, 2019a ) in three other studies.…”
Section: Integrated Analysis and Discussionmentioning
confidence: 88%
See 3 more Smart Citations